Study Of Trace Elements In Hair From A Selected Male Population In Penang And Fallujah Using Xrf - Aldroobi, Khalid Saleh Ali (2014)
The state of Penang encompasses an industrial region with a potential for the existence of a variety of industrial pollutants which would certainly have a possible impact on the environment and the people. Similarly, the city of Fallujah in Iraq has been exposed to a lot of toxic materials in the form of chemical weapons during the war in 2004. Such exposure would certainly have a detrimental impact on the environment and the people in these two cities. Although it has been argued that knowledge of the natural levels of trace elements in hair is extremely essential for assessing the degree of human contamination in areas where these elements are expected to show anomalous concentrations, these data from hair samples from Penang and Fallujah are not available. In this study, arsenic, mercury, lead, iron, copper and zinc in hair samples from Penang and Fallujah were analysed to assess the environmental uptake of these elements. The natural levels of trace elements in hair were hence monitored as reference values for the assessment of the possible human contamination levels. In this work, the concentrations of Hg, As, Cu, Zn, Fe and Pb in human scalp hair of 100 residents of Penang and 28 in Fallujah were determined using XRF.